Association of serum complement C3 level with disease severity in primary pterygium - Yun, Young In; Heo, Jung Sun; Lee, Seung Hyeun; Kim, Kyoung Woo (Frontiers in Medicine, 2025)
PurposeTo investigate whether various systemic inflammatory and immunologic markers—including complement C3, C4, antinuclear antibodies (ANA), rheumatoid factor (RF), and other autoantibodies—are associated with the clinical severity of primary nasal pterygium.MethodsWe retrospectively reviewed 26 eyes from patients with primary nasal pterygium. Serum complement levels (C3, C4), erythrocyte sedimentation rate (ESR), and autoimmune markers (ANA, RF, perinuclear anti-neutrophil cytoplasmic antibody [P-ANCA], cytoplasmic ANCA [C-ANCA], human leukocyte antigen [HLA]-B51, HLA-B27, anti-Ro [SSA], and anti-La [SSB]) were measured. Pterygium severity was graded using T (stromal translucency), V (vascularity), and the loss of plica semilunaris (LPS).ResultsAmong 26 patients (mean age 52.9 ± 14.9 years; 42.3% female), 61.5% tested positive for ANA. However, neither ANA positivity nor titer correlated with T, V, or LPS grades. Five patients (19.2%) had low C3 (<90 mg/dL). Although C4 and ESR did not correlate with disease severity, C3 levels showed a significant inverse correlation with the T grade (r = −0.477, p = 0.014). No significant association was found between C3 and the V grade or LPS, suggesting that severe stromal changes (T3) may be linked to modest complement consumption.ConclusionLower serum C3 levels were associated with advanced stromal opacification in pterygium, indicating possible complement activation in severe disease. While ANA was frequently positive, it did not correlate with clinical severity. These findings suggest that complement C3 may serve as a potential biomarker for advanced pterygium.